First, multiply each term with each parenthesis by the term outside the parenthesis:
0 = color(red)(4)(n - 4) - color(blue)(6)(n - 4)
0 = (color(red)(4) xx n) - (color(red)(4) xx 4) - (color(blue)(6) xx n) - (color(blue)(6) xx -4)
0 = 4n - 16 - 6n - (-24)
0 = 4n - 16 - 6n + 24
Next, on the right side of the equation, group and combine like terms:
0 = 4n - 6n - 16 + 24
0 = (4 - 6)n + 8
0 = -2n + 8
Then, subtract color(red)(8) from each side of the equation to isolate the n term while keeping the equation balanced:
0 - color(red)(8) = -2n + 8 - color(red)(8)
-8 = -2n + 0
-8 = -2n
Now, divide each side of the equation by color(red)(-2) to solve for n while keeping the equation balanced:
(-8)/color(red)(-2) = (-2n)/color(red)(-2)
4 = (color(red)(cancel(color(black)(-2)))n)/cancel(color(red)(-2))
4 = n
n = 4